Algoritmo para reconfiguração de sistemas de distribuição de energia elétrica baseado em evolução diferencial - Oliveira, Caio Francisco Vasconcelos de (2016)
The electric power produced in Brazil goes through a long process before reaching the final consumers: industries, urban and rural centers, etc. Such process consists on electric power generation, transmission and distribution. However, inherent losses, due to the Joule effect, are associated with these processes. Futhermore, distribution electric newtworks are subject at all times to external agents which can cause failures through short circuits and conductor drops, leading the system to an abnormal state of operation, requiring isolation of the faulty section and the energy restoration of the affected part of the system. Both cases can be reduced with the system reconfiguration. This may provide the ohmic loss reduction, when it is in normal operating condition, and/or ensure a network condition in which the system defect is isolated and a maximum number of affected loads are restored. This work presents a methodology for the electric energy distribution systems based on the metaheuristics of Differencial Evolution. Graph concepts and node-depth representation are used to more efficiently apply the backward/forward sweep method for calculating the power flow in the proposed system configurations. The proposed methodoloy uses as input data values of active and reactive powers connected to the buses of the distribution system, topology information, initial network configuration, conductors and supply sources capacities. As results, the network reconfiguration with minimum losses and minimum number of desenergized loads is presented. Typical operational restrictions of radial electrical networks are considered such as: maximum conduction capacity of the conductors, supply capacity of the sources and allowable voltage levels. Tests with the algorithm were performed for the electrical IEEE systems of 16, 33, 69 and 83 buses and the results were compared with other methodologies. The results of the tests indicate that the implementation of the methodology in the service of distribution of electric power in networks of power utilities can contribute to a better use of its assets and an improvement of its quality of service indicators.